Збройна агресія російської федерації проти України як загроза системі колективної безпеки - Войціховський, А. В.; Voytsihovskyi, A. V.; Бакумов, О. С.; Bakumov, O. S.; Андрій Войціховський (Право і безпека. – 2023. – № 1 (88). – С. 134-145, 2023)
Розкрито основні інституціональні проблеми системи колективної безпеки в умовах збройної агресії російської федерації проти України. Визначено пріоритетне значення питання забезпечення колективної безпеки, зважаючи на агресивну зовнішню політику росії. Система колективної безпеки обґрунтовано розглядається як головний критерій існування та розвитку дружніх відносин між державами та підтримання міжнародного правопорядку. У зв’язку з виробленням нових підходів і напрямів розвитку стратегій міжнародних організацій, які складають систему колективної безпеки, надано аналіз діяльності Організації Об’єднаних Націй, Організації Північноатлантичного договору і Організації з безпеки і співробітництва в Європі як реакції міжнародної спільноти на збройне вторгнення російської федерації в Україну. Запропоновано переосмислити парадигму забезпечення колективної безпеки. Окреслено роль України у побудові нової системи колективної безпеки.

The Russian Federation’s unprovoked and unjustified war against Ukraine has changed the entire security environment, which will have long-term threatening consequences for the entire collective security system. The issue of forming an effective system of collective security is relevant not only for the international community, which is explained by its absolute importance in maintaining international law and order, but also for Ukraine in order to restore its state sovereignty and territorial integrity in countering Russian armed aggression. The purpose of the article is to clarify the essence of the collective security system, to analyze the activities of the most influential international security organizations (UN, NATO and OSCE) since the outbreak of the Russian-Ukrainian war and to assess their ability to end this war, to formulate problematic issues regarding the functioning of the existing collective security system, and to argue for the need to build a new collective security system with a definition of Ukraine's role and place in it. The conclusion of the study is that the modern system of collective security should be understood as a state of international relations that excludes violation of the general peace, threats to the security of states and peoples, and counteraction to acts of aggression, implemented by joint efforts of participating states at the global or regional levels. The collective security system is usually implemented through the activities of the UN, NATO and the OSCE in maintaining international law and order. However, in the context of numerous conflicts, including the Russian-Ukrainian war, there are more and more complaints about the activities of the UN, in particular the UN Security Council as the main body responsible for maintaining international peace and security. At the same time, the role of the UN should not be minimized, as the documents adopted by it are important for improving the collective security system and the international mechanism for bringing the aggressor state to justice. Despite the significant resistance of the Russian Federation, the UN, NATO and the OSCE strongly condemn Russia’s aggressive war against Ukraine and continue to provide our country with comprehensive support.

Раскрыты главные институциональные проблемы системы коллективной безопасности в условиях вооруженной агрессии российской федерации против Украины. Определено приоритетное значение вопроса обеспечения коллективной безопасности ввиду агрессивной внешней политики россии. Система коллективной безопасности рассматривается как главный критерий существования и развития дружеских отношений между государствами и поддержания международного правопорядка. В связи с выработкой новейших подходов и направлений развития стратегий международных организаций, составляющих систему коллективной безопасности, дается анализ деятельности Организации Объединенных Наций, Организации Североатлантического договора и Организации по безопасности и сотрудничеству в Европе как реакции международного сообщества на вооруженное вторжение российской федерации в Украину. Аргументировано предлагается переосмыслить парадигму обеспечения коллективной безопасности. Обозначена роль Украины в построении новой системы коллективной безопасности.
Armed aggression of the Russian Federation against Ukraine as a threat to the collective security system
Вооруженная агрессия российской федерации против Украины как угроза системе коллективной безопасности
Keywords: Кримінологія. Criminology. Криминология; Наукові публікації. Scientific publications. Научные публикации; Україна. Ukraine. Украина; Міжнародне право .International Law. Международное право; колективна безпека; collective security; коллективная безопасность; збройна агресія; armed aggression; вооруженная агрессия; ООН; UN; НАТО; NATO; ОБСЄ; OSCE; ОБСЕ; міжнародний правопорядок; international legal order; международный правопорядок